Factors Affecting Glomerular Filtration Rate and Length of Hospitalization in Pediatric Acute Poststreptococcal Glomerulonephritis: A Decade-Long Observational Study - Doğukan Mustafa Keskin; Pınar Belviranlı Keskin; Mehmet Kocaoğlu; Alper Yıldırım; Oğuz Eğil (Güncel Pediatri)
Introduction: Acute poststreptococcal glomerulonephritis (APSGN) remains a significant public health concern, especially in pediatric populations. This decadelong observational study aims to provide a comprehensive exploration of pediatric APSGN, emphasizing on factors those influencing glomerular filtration rate (GFR) and also contributing to prolonged hospitalization. Materials and Methods: The single-center, observational, retrospective study was conducted from January 2010 to December 2020 and included children aged 3-18 years diagnosed with APSGN. Diagnostic criteria included hematuria, decreased serum complement-3 levels, and evidence of recent streptococcal infection. Data extracted from medical records encompassed demographic details, clinical features, and a range of laboratory parameters. Results: Forty-four patients with APSGN were included (mean age: 8.65±3.31 years), 54.55% of whom were male. Hematuria was present in all cases (macroscopic hematuria in 77.27% of patients), edema in 63.64% of cases, and hypertension in 50.00% of cases. There was a negative correlation between inflammatory markers (C-reactive protein, neutrophil count, and neutrophil-to-lymphocyte ratio) and GFR (r: -0.511, r: -0.302, r: -0.380; p :< 0.05 respectively). Decreased GFR, albumin, and complement-3 levels (r: -0.361, r: -0.442, r: -0.315; p :< 0.05, respectively), and increased urine density and urinary protein excretion, correlated significantly with prolonged hospitalization r: 0.413, r: 0.362; p:< 0.05, respectively). Conclusion: Despite the generally favorable prognosis of pediatric APSGN, this study highlights the potential for severe complications. Elevated inflammatory markers signal severe renal involvement, while decreased GFR, albumin, and complement-3 levels, as well as increased urine density and protein excretion, lead to extended hospital stays. These findings may be used for anticipating patient outcomes and optimizing resource utilization in pediatric APSGN care.